Ultrasound-guided peripheral venous cannulation in critically ill patients: a practical guideline - Blanco, Pablo (Ultrasound J, 2019)
BACKGROUND: Up to one-third of critically ill patients have difficult intravenous access (DIVA). This occurs often in obese patients, those with generalized edemas or in patients with previous venous cannulations. In DIVA patients, the conventional technique often fails. In contrast, ultrasound-guided cannulation has demonstrated a high success rate, improving patient satisfaction and even a reduction in the need of central venous lines. However, a high rate of premature catheter failure has been shown in cannulations performed by ultrasound guidance and thus a comprehensive knowledge of several aspects related to this procedure is mandatory to improve cannulation success, avoid complications and lengthen the survival of the catheter. MAIN TEXT: Several practical issues related to peripheral venous cannulation are described: peripheral venous anatomy, vein size and catheter selection, distance from skin to vein, insertion angle and selection of the catheter length, cannulation technique itself (out-of-plane or in-plane) and checking catheter position. CONCLUSION: Key concepts regarding ultrasound-guided peripheral vein cannulation should be well known for practitioners, aiding in improving cannulation success and catheter dwell time, and avoiding complications.